Suicidal gene therapy in an NF-κB-controlled tumor environment as monitored by a secreted blood reporter - Zalloua, P. A. (2011)
The nuclear factor-κB (NF-κB) is known to be activated in many cancer types including lung, ovarian, astrocytomas, melanoma, prostate as well as glioblastoma, and has been shown to correlate with disease progression. We have cloned a novel NF-κB-based reporter system (five tandem repeats of NF-κB responsive genomic element (NF; 14 bp each)) to drive the expression cassette for both a fusion between the yeast cytosine deaminase and uracil phosphoribosyltransferase (CU) as a therapeutic gene and the secreted Gaussia luciferase (Gluc) as a blood reporter, separated by an internal ribosomal entry site (NF-CU-IGluc). We showed that malignant tumor cells have high expression of Gluc, which correlates to high activation of NF-κB. When NF-κB was further activated by tumor necrosis factor-α in these cells, we observed up to 10-fold increase in Gluc levels and therefore transgene expression in human glioma cells served to greatly enhance the sensitization of these cells to the prodrug, 5-fluorocytosine both in cultured cells and in vivo subcutaneous tumor xenograft model. This inducible system provides a tool to enhance the expression of imaging and therapeutic genes for cancer therapy.